Unique environmental effects on physical activity participation: a twin study. - Glen E Duncan; Jack Goldberg; Carolyn Noonan; Anne Vernez Moudon; Philip Hurvitz; Dedra Buchwald (PLoS ONE)
Background The health benefits of regular physical activity are well established. However, the relative contribution of heritable and environmental factors to physical activity participation remains controversial. Using a cut-point of 60 minutes of total activity per week, data from the GenomEUtwin project revealed consistent genetic influence on physical activity participation in 37,051 twin pairs from seven countries. We hypothesized that the heritability of physical activity participation would be attenuated using the CDC/ACSM recommended minimum threshold of 150 minutes of moderate intensity activity per week. Methods Data were obtained from 1,389 twin pairs from the community-based University of Washington Twin Registry. Twin similarity in physical activity participation using both cut-points was analyzed using tetrachoric correlations and structural equation modeling in all same-sex pairs. Results Correlations were higher in monozygotic (r(MZ) = 0.43, 95% CI = 0.33-0.54) than dizygotic pairs (r(DZ) = 0.30, 95% CI = 0.12-0.47) using the 60 minute cut-point. However, differences were attenuated using the 150 minute standard (r(MZ) = 0.30, 95% CI = 0.20-0.40; r(DZ) = 0.25, 95% CI = 0.07-0.42). Using the lower cut-point, the best fitting model of twin resemblance only included additive genetics and unique environment, with a heritability of 45%. In contrast, using the higher threshold, the best fitting model included the common and unique environment, with the unique environment contributing 72% of the variance. Conclusion Unique environment factors provide the strongest influence on physical activity participation at levels recommended for health benefits.